2018
DOI: 10.17811/aula_abierta.47.4.2018.463-470
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction degree of English teachers of Preschool and Primary Education in the Principality of Asturias

Abstract: This paper analyses the satisfaction level of teachers of English in Preschool and Primary Education in the Principality of Asturias (Spain). The sample was composed of 238 teachers from 68 schools and the research tool was a 45-item questionnaire. Data were processed with SPSS, and variance analyses were performed to assess the impact of the variables considered. The main results confirm that general satisfaction is rather high, although it is possible to identify improvement proposals in relation to the soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Music is also a testimony of culture from a holistic perspective (Brooks et al, 2020). Furthermore, research has identified a prominent influence which music training has on students of foreign languages (Fernández-Costales andGonzález-Riaño, 2018, Flaugnacco et al, 2015;Posedel et al, 2012;Swaminathan et al, 2018).…”
mentioning
confidence: 99%
“…Music is also a testimony of culture from a holistic perspective (Brooks et al, 2020). Furthermore, research has identified a prominent influence which music training has on students of foreign languages (Fernández-Costales andGonzález-Riaño, 2018, Flaugnacco et al, 2015;Posedel et al, 2012;Swaminathan et al, 2018).…”
mentioning
confidence: 99%